The effect of nutrient limitation on growth and lipid production of Chlorella vulgaris in recirculating aquaculture system’s effluent - Nakandalage, Bernadeth (2024)
Cultivating microalgae has gained significant attention in recent years. They can produce various valuable biochemical compounds, such as lipids. Enhancing the production of lipid can be accomplished by limiting nutrient availability (e.g. nitrogen (N) or sulphur (S)). Cultivating microalgae in wastewater allows uptake of nutrients from wastewater thereby facilitating water purification. I measured the growth, lipid content, fatty acid composition and nutrient uptake efficiencies (nitrate (NO3) and phosphate (PO4)) of a green microalga Chlorella vulgaris. This microalga was cultivated in both nutrient limited (N and S) and non-limited (as control treatment) conditions. Effluent from a recirculating aquaculture system (RAS) housing rainbow trout (Oncorhynchus mykiss) was used to grow C. vulgaris. N limitation was achieved by changing the N:P ratio (N:P/2, N:P/4) in RAS effluent, while S limitation was achieved by transferring C. vulgaris into S-free algal culture media after initial growth in the RAS effluent (a two-stage cultivation method). C. vulgaris was cultivated in photobioreactors under LED lights and aerated with ambient room air. It was expected that nutrient limitation would increase the lipid content (% in DW) in C. vulgaris with reduced growth. However, under N-limited conditions, the lipid content of C. vulgaris decreased compared to the control, as N limitation was not effectively achieved. In contrast, S limitation resulted in an increase in lipid content compared to the control. The growth and NO3 uptake efficiency did not significantly differ between nutrient-limited and non-limited conditions. However, the PO4 uptake efficiency was higher in N limited treatments than in control. These findings support that cultivating C. vulgaris under S limitation, as two-stage cultivation, is an appropriate way to get a substantial amount of highly valuable microalgae biomass with moderate lipid content. Growing microalgae by utilizing nutrient rich RAS effluent helps with recycling nutrients and reduces environmental pollution, thereby promoting a more sustainable and eco-friendly aquaculture system.